Pediatric dentinogenic ghost cell tumor: a case report and review of the literature - Wang, Linlin; Han, Jingchao; Xie, Jianli; Tian, HongSheng (Frontiers in Oncology, 2025)
Dentinogenic ghost cell tumor (DGCT) is a rare odontogenic neoplasm that presents with nonspecific clinical manifestations and imaging features. It is more prevalent in elderly patients, with cases in children being extremely rare. This article presents a case study of a 10-year-old male patient who exhibited symptoms of swelling and pain in the left cheek for a duration of two weeks. Cone beam computed tomography (CBCT) demonstrated a hypodense lesion involving the left maxilla, with extension into the maxillary sinus and buccal cortical expansion. The patient underwent decompression, and histopathological examination of the intraoperative specimen suggested a diagnosis of calcifying odontogenic cyst (COC). One year after decompression, the patient underwent a tumor resection and the diagnosis of DGCT was confirmed by the post-operative pathology. Six months after tumor resection, CBCT showed complete bone remodeling in the lesion area. The patient is currently undergoing regular follow-up. This case provides an important reference for the diagnosis and treatment of pediatric DGCT, helping clinicians to develop individualised treatment plans.